HUBUNGAN KEDISIPLINAN DAN MOTIVASI TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI PESERTA DIDIK SMP MUJAHIDIN PONTIANAK - Nurfajari, Risti; Simanjuntak, Victor G; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aims of this research was to determine the significant relationship between discipline and motivation with physical education learning students’ outcomes of  VIII class SMP Mujahidin Pontianak. The method used in this research is quantitative descriptive method with the form of multiple correlation research. The subjects of this study were all of  students of  VIII class of  SMP Mujahidin Pontianak with a total students are 15 students. In this study the data were collected using a questionnaire for disciplinary and motivational variables, while learning outcomes use value documentation report cards physical education subjects even semester 2018/2019. The results showed that there was a significant relationship between discipline and motivation with physical education learning outcomes of VIII grade studentsof  SMP  Mujahidin Pontianak as evidenced by rx1x2y= 0.897, rx1x2y= 0.804, fcount= 24.707 which has a percentage of 80.46% with a very strong category. Based on these findings it could  be concluded that there was a positive and significant relationship between discipline and motivation with the learning outcomes of VIII class Physical Education in SMP Mujahidin Pontianak. Thus these two factors could be used as predictors of learning success of students, especially in physical education subjects and other subjects in general.  Keywords: Discipline, Motivation, Physical Education Learning Outcomes